Use of Indigenous Hanseniaspora vineae and Metschnikowia pulcherrima Co-fermentation With Saccharomyces cerevisiae to Improve the Aroma Diversity of Vidal Blanc Icewine - Zhang, Bo-Qin; Shen, Jing-Yun; Duan, Chang-Qing; Yan, Guo-Liang (Frontiers in Microbiology, 2018)
Using novel non-Saccharomyces strains is regarded as an effective way to improve aroma diversity of wines expected by consumers. The non-Saccharomyces Hanseniaspora vineae and Metschnikowia pulcherrima have good aromatic properties in the production of table wine. However, no detailed information is available on their performances in icewine fermentation. In this study, simultaneous and sequential fermentation trials of indigenous M. pulcherrima CVE-MP20 or H. vineae CVE-HV11 with S. cerevisiae (SC45) were performed in 50-L fermenter of Vidal icewine, respectively. The results showed that SC45 co-fermented with different non-Saccharomyces strains could generate distinct aroma quality of icewine compared to four S. cerevisiae strain monocultures as evidenced by principal component analysis (PCA). Mixed fermentation of MP20/SC45 produced higher contents of acetate esters and β-damascenone with lower C6 alcohols relative to SC45 monoculture. Interestingly, HV11/SC45 generated the highest amounts of C6 alcohols ((Z)-3-hexen-1-ol and (E)-3-hexen-1-ol), higher alcohols (isobutanol, isopentanol and 2-phenylethanol), acetate esters (2-phenethyl acetate and isoamyl acetate), cis-rose oxide, β-damascenone and phenylacetaldehyde. Compared to simultaneous inoculation, sequential inoculation could achieve higher aroma diversity and produce higher intensity of fruity, flowery and sweet attributes of icewine as assessed by calculating the odor activity values (OAVs). Our results verified the desired enological characteristics of H. vineae strain in icewine fermentation, and also demonstrated that using indigenous non-Saccharomyces and Saccharomyces strains is a feasible way to improve aroma diversity of icewine products, which could provide an alternative way to meet the requirement of wine consumers for diversified aromatic quality.